The Effect of Green Risk and the Attitude to Green Purchase Intention with Green Trust as Mediation - Baskara Dwi Adi Syahputra; Yulia Hendri Yeni (Institute of Computer Science (IOCS), 2021)
This study aims to examine and analyze the effect of green risk and attitudes towards green purchase intention mediated by green trust on herbal medicine consumers in Padang city, West Sumatra. The population is all herbal medicine consumers in Padang City. The sampling method used was purposive sampling. The research data collection was carried out by distributing questionnaires to 142 respondents. Processing and data analysis was done using SmartPLS. Green risk has positive and significant effect on green purchase intention. Attitudes have positive and significant effect on green purchase intention. Green risk has positive and insignificant effect on green trust. Attitude has positive and significant effect on green trust. Green trust has positive and significant effect on green purchase intention. Green trusts act as mediation between green risk and green purchase intention. Green trust acts as a partial mediation between attitudes and green purchase intention.